Olfactory Landmark Information in Wayfinding: Implicit and Explicit Processing of Sensory Information in Spatial Orientation - Schwarz, Mira; Justus Liebig University Giessen (My University, 2025)
Human navigation research has long been dominated by a vision-centered perspective, often neglecting the role of other sensory modalities, particularly olfaction. Across two empirical studies and a state-of- the-art review, this dissertation examines how visual and olfactory cues guide human wayfinding. The first study shows that switching between visual and olfactory landmark information leads to switching costs, reflected in longer decision times and reduced wayfinding accuracy. These results diverge from earlier findings of absent switching costs between auditory and visual landmarks, suggesting that odors and images are initially processed in separate cognitive systems and require cognitively demanding cross-modal translation. The second study demonstrates that olfactory landmarks can support navigation even without explicit recognition. Across two testing times one month apart, wayfinding performance in a virtual maze was highest when olfactory cues were processed implicitly, whereas performance with visual landmarks was higher when processed explicitly. These results suggest distinct implicit mechanisms in the olfactory system and highlight the importance of non-conscious contributions to navigation. The third publication is a review article on the sense of smell in human navigation, summarizing empirical findings, challenging the misconception that humans have a poor sense of smell, and outlining why this ability has been largely overlooked. Together, the studies provide converging evidence that olfactory cues can meaningfully support human wayfinding, largely through implicit processes. Based on these insights, the dissertation proposes a Multimodal Integrative Model distinguishing implicit from explicit processes across visual and olfactory modalities, highlighting their joint role in flexible multimodal navigation.
Keywords: wayfinding; olfaction; olfactory; landmark; ddc:150